1998
DOI: 10.1046/j.1365-4362.1998.00382.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in leprosy, II. Effect of treatment on serum cytokines in leprosy

Abstract: MDT caused a reduction in serum cytokines correlated with a reduction in the bacterial burden. It is advisable to continue MDT for PB patients for 1 year. Serum IL-1beta levels may have a prognostic value for the susceptibility of leprosy patients to the development of reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
(14 reference statements)
1
11
1
1
Order By: Relevance
“…This finding disagrees with that of Moubascher et al 16 , who demonstrated a significant reduction in IL-1β serum levels and other molecules (IL-2R and IL-10) after one year of treatment in 36 leprosy cases. However, for this analysis, the present sample consisted of only seven patients, being considered too small for the researchers to make inferences.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding disagrees with that of Moubascher et al 16 , who demonstrated a significant reduction in IL-1β serum levels and other molecules (IL-2R and IL-10) after one year of treatment in 36 leprosy cases. However, for this analysis, the present sample consisted of only seven patients, being considered too small for the researchers to make inferences.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding agrees with that observed by Moubasher et al 16 , in which nontreated leprosy patients exhibited significantly higher IL-1β serum levels and other molecules (IFN -γ, IL-2R, IL-10 and TNF-α) detected by the ELISA test compared to healthy controls. Therefore, we may deduce that IL-1β release in leprosy cases is an indication of the activation of a cell-mediated immune response to the bacillus, according to the observation of Watson et al 35 , who quantified the production of IL-1β and IL-2 by mononuclear adhering cells from the peripheral blood of patients with different forms of leprosy.…”
Section: Discussionsupporting
confidence: 93%
“…In this case, cytokine of leprosy patients produced as response to immune stimulation by M. leprae antigen, and when this antigen reduced after treatment, cytokine production also decreased and it may reduced to normal level as in healthy subject if this antigen is totally diminished [15].…”
Section: Discussionmentioning
confidence: 83%
“…Regarding the TLR4 gene, we observed greater production of IL-1-β and IL-17 between carriers of the A allele in the exonic SNP rs1927914. IL1-β is essential for the amplification of the T-cells specific immune response and its levels tend to decrease after the multidrug therapy (Moubasher et al 1998). This cytokine is also produced in high concentrations in multibacillary patients (Madan et al 2011).…”
Section: Discussionmentioning
confidence: 99%